2022
DOI: 10.1038/s41433-022-02360-4
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography imaging biomarkers associated with neovascular age-related macular degeneration: a systematic review

Abstract: The aim of this systematic literature review is twofold, (1) detail the impact of retinal biomarkers identifiable via optical coherence tomography (OCT) on disease progression and response to treatment in neovascular age-related macular degeneration (nAMD) and (2) establish which biomarkers are currently identifiable by artificial intelligence (AI) models and the utilisation of this technology. Following the PRISMA guidelines, PubMed was searched for peer-reviewed publications dated between January 2016 and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 121 publications
(232 reference statements)
0
21
0
Order By: Relevance
“…At the discretion of the investigator, extension of the retreatment interval was allowed if stability of signs, such as sub retinal fluid was suspected. The presence of disease activity at outset of treatment is associated with a poor outcome but some biomarkers such as sub retinal fluid if present during the disease journey, may be tolerated, if stable, with no apparent adverse outcomes at least in the medium term (Hanson et al, 2022). Explanations for this burden of treatment include how the MATE‐EX study may have been influenced by the COVID‐19 pandemic so that further extensions of a retreatment interval in some were not tried, or the retreatment criteria being too intolerant of potential markers of disease activity (when activity was not present) or an unusual participant population.…”
Section: Discussionmentioning
confidence: 99%
“…At the discretion of the investigator, extension of the retreatment interval was allowed if stability of signs, such as sub retinal fluid was suspected. The presence of disease activity at outset of treatment is associated with a poor outcome but some biomarkers such as sub retinal fluid if present during the disease journey, may be tolerated, if stable, with no apparent adverse outcomes at least in the medium term (Hanson et al, 2022). Explanations for this burden of treatment include how the MATE‐EX study may have been influenced by the COVID‐19 pandemic so that further extensions of a retreatment interval in some were not tried, or the retreatment criteria being too intolerant of potential markers of disease activity (when activity was not present) or an unusual participant population.…”
Section: Discussionmentioning
confidence: 99%
“…Nine of the 12 clinical trials used a change in macular fluid as a disease activity criterion. Qualitative interpretation of structural OCT images for nAMD disease biomarkers is well established in clinical practice as a way of determining improvement, stability or worsening of nAMD disease activity [ 23 ]. However, a recent review identified 11 features or biomarkers, some with more robust evidence base to support their use over other less well-established biomarkers where consensus is still lacking [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative interpretation of structural OCT images for nAMD disease biomarkers is well established in clinical practice as a way of determining improvement, stability or worsening of nAMD disease activity [ 23 ]. However, a recent review identified 11 features or biomarkers, some with more robust evidence base to support their use over other less well-established biomarkers where consensus is still lacking [ 23 ]. Even when considering intraretinal fluid as an imaging biomarker of nAMD disease activity, clinicians need to attempt to distinguish IRF associated with atrophy and tubulation from IRF associated with worsening exudative, nAMD.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers have emerged as valuable tools in ophthalmology, providing measurable indicators of disease processes and treatment responses. 1 Although imaging is widely used in the study of retinal diseases, 2 5 it is not suitable for detecting the molecular changes associated with ocular pathophysiology. By complementing imaging investigations, molecular factors (including proteins, lipids, metabolites, miRNAs, and extracellular DNA, for example) in aqueous humor (AH) and vitreous humor (VH) have the potential to offer insights into the pathophysiology of retinal disorders.…”
Section: Introductionmentioning
confidence: 99%